Effect of Supplemented Food with Wild Mango (Irvingia Smithii) Almond Powder on the Weight Growth of Mice - V.G. Gindo Mbaya; P.E. Sumbu Zola; D. Mayele Kipoy; V.E. Tshiombe Mulamba; E. Kimbemuken Thasur (Britain International for Academic Research (BIAR) Publisher, 2023)
Almond powder of Irvingia smithii has been incorporated, at the doses of 25 and 50 %, in mice standard ration (prepared by Matadi mill), at INRB, composed of wheat flour, wheat bran and pellets for rabbits to evaluate weight gain, live weight gain and feed conversion and to assess motor activity after 50 days of feeding. Results showed an average increase in live weight gain of 31.08% and 8.36% for the groups of mice fed food supplemented with Irvingia smithii almond powder respectively at 25% and 50% higher than the group of control mice fed exclusively with the standard food. On the other hand, the food consumption index (F.C.I) was very low for the group of mice fed with the food supplemented at 50% (F.C.I. 27.73) and low for the group of mice fed 25% supplemented food (F.C.I. 64.83) compared to the control group (F.I.C. 108,14). In addition, the groups of mice fed the supplemented food did not show motor weakness, even fewer respiratory complications or health problems compared to the control during these 50 days of observation. Live weight gain sufficiently demonstrates the nutritional value of the kernel of I. smithii.